1983
DOI: 10.1159/000123452
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prostaglandins in Neuroendocrine Junctions:Studies in the Pineal Gland and the Hypothalamus

Abstract: This article discusses current experimental evidence indicating a role for prostaglandins (PGs) in pineal and median eminence neuroendocrine junctions. Both tissues release PGs, particularly of the E series, upon exposure to norepinephrine (NE) and through α-adrenoceptors. Exposure of pineal and median eminence explants to nanomolar concentrations of PGE2 augments melatonin and GnRH release, respectively. In the pineal gland, this effect appears to be linked to the stimulation of adenylate cyclase. Both in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 66 publications
1
8
0
1
Order By: Relevance
“…Other investigators have also shown that activation of pineal ai-adrenergic receptors affects pi neal function. For example, agonists of these receptors in crease pineal prostaglandins [3] and also increase the effect of |3-adrenoreceptor agonists on induction of the enzyme serotonin-N-acetyltransferase [17][18][19]. The results of the present study are consistent with these findings, especially the latter, since 5-HT antagonizes the stimulatory effect of NE on cyclic adenosine monophosphate in pineal [28].…”
Section: Discussionsupporting
confidence: 87%
“…Other investigators have also shown that activation of pineal ai-adrenergic receptors affects pi neal function. For example, agonists of these receptors in crease pineal prostaglandins [3] and also increase the effect of |3-adrenoreceptor agonists on induction of the enzyme serotonin-N-acetyltransferase [17][18][19]. The results of the present study are consistent with these findings, especially the latter, since 5-HT antagonizes the stimulatory effect of NE on cyclic adenosine monophosphate in pineal [28].…”
Section: Discussionsupporting
confidence: 87%
“…Activation of PGE2 synthesis is considered an essential step in the sequence of events leading to LHRH release from hypothalamic nerve terminals [6,22,27], This activa tion appears to be effected mainly by norepinephrine (NE) [5,8,25] even though epinephrine and dopamine are also capable of inducing some PGE2 release [25]. NE interacts with a-adrenergic receptors to stimulate the release of PGE2, which in turn induces LHRH release [28].…”
Section: Discussionmentioning
confidence: 99%
“…) and these are involved in the reduction by melatonin of free radical formation by mitochondria (Acuna‐Castroviejo et al . ), cyclooxygenase (COX) during prostaglandin synthesis (Cardinali & Ritta, ), and uncoupled nitric oxide synthase (NOS) (Tapias et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin scavenges hydroxyl (Poeggeler et al 1993), carbonate (Hardeland et al 2003) and peroxynitrite (Hardeland et al 2007) radicals by receptor-independent mechanisms, probably involving its aromatic indole ring structure. Classical G-protein-coupled melatonin receptors occur in the cardiovascular system (Dubocovich & Markowska, 2005;Paulis et al 2012) and these are involved in the reduction by melatonin of free radical formation by mitochondria (Acuna-Castroviejo et al 2007), cyclooxygenase (COX) during prostaglandin synthesis (Cardinali & Ritta, 1983), and uncoupled nitric oxide synthase (NOS) (Tapias et al 2009). Melatonin also acts via its receptors to stimulate production of free radical scavengers such as superoxide dismutase, catalase and glutathione peroxidase and reductase (López et al 2006).…”
Section: Introductionmentioning
confidence: 99%